Effect of Entrepreneurial Characteristics on the Work-life Balance of Women Entrepreneurs in the Chhattisgarh Region - Shreya Kushwaha, Raj Maurya, Shubham Rajpal (European Economic Letters (EEL), 2024)
The involvement of women as an entrepreneur has steadily expanded, considerably contributing to economic development and social advancement. Women entrepreneurs confront unique problems in balancing their lives at home and at business, especially in regions where conventional gender norms exist, such as Chhattisgarh, India. The intent of the study is to investigate the effect of entrepreneurial qualities on work-life balance among women entrepreneurs in Chhattisgarh. The study uses exploratory statistics to obtain data from 200 women entrepreneurs utilizing a questionnaire schedule. A sample of 200 was analysed through SPSS and the study has employed statistical tools for analysis are factor analysis, reliability, correlation, and regression to examine the hypothesis of the study. The study identifies various entrepreneurial characteristics, including industry and cultural context, social characteristics, work-life balance, personal characteristics, and innovative strategies and examines their role in shaping the work-life balance of women entrepreneurs. The findings reveal that cultural and societal expectations often challenge women entrepreneurs' ability to balance their professional and personal lives. Industrial and cultural factors emerge as significant determinants, with varying degrees of support affecting work-life balance outcomes. By addressing the specific entrepreneurial characteristics identified in this study, policymakers, and business support organizations, may recognize the particular obstacles faced by women entrepreneurs in Chhattisgarh.